Latitudinal Characteristics of Nighttime Electron Temperature in the Topside Ionosphere and Its Dependence on Solar and Geomagnetic Activities - Jianyun Liang; Jiyao Xu; Kun Wu; Ji Luo (Remote Sensing, 2024)
This study investigates the latitudinal characteristics of the nighttime electron temperature, as observed by the Defense Meteorological Satellite Program F16 satellite, and its dependence on solar and geomagnetic activities between 2013 and 2022 in the topside ionosphere, only for the winter hemispheres. The electron temperature in both hemispheres exhibited a low-temperature zone at the equator and a double high-temperature zone at the sub-auroral and auroral latitudes along the magnetic latitude. In addition, we further studied the temperature crest/trough positions in the temperature zone at different latitudes. As the solar activity intensity decreased (increased), the temperature trough position at the equator shifted from the Southern (Northern) to the Northern (Southern) Hemisphere, and the temperature double-crest positions at the sub-auroral and auroral latitudes gradually approached (moved away from) each other. Furthermore, during the geomagnetic disturbance time, the temperature double-crest positions both moved toward lower latitudes, but the temperature trough position was not sensitive to geomagnetic activity. Our analysis demonstrates that the values and correlations of the electron temperature and density varied in different temperature characteristic zones (the temperature crest/trough positions ±2°), possibly due to the different energy control factors of the electrons at different latitudes. This may also indirectly indicate the energy coupling process between the topside ionosphere and different regions at different latitudes.